2017
DOI: 10.1126/scisignal.aal4055
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-activated ion channels in neural crest cells confer maternal fever–associated birth defects

Abstract: Birth defects of the heart and face are common, and most have no known genetic cause, suggesting a role for environmental factors. Maternal fever during the first trimester is an environmental risk factor linked to these defects. Neural crest cells are precursor populations essential to the development of both at-risk tissues. We report that two heat-activated transient receptor potential (TRP) ion channels, TRPV1 and TRPV4, were present in neural crest cells during critical windows of heart and face developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
88
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 80 publications
3
88
1
Order By: Relevance
“…To study the effects of thermal stress on morphogenesis, dissection and direct observation of embryos is critical. Based on our results and comparisons with mammals (Walsh et al., ; Edwards, ; Hutson et al., ), these may be the most thermally sensitive stages of embryonic development for diverse vertebrate species. Within mammals and birds, thermal stress during morphogenesis may cause craniofacial abnormalities, neural tube defects, or mental retardation (Webster & Edwards, ; Shiota, ; Walsh et al., ; Edwards, ; Edwards, Saunders, & Shiota, ).…”
Section: Discussionmentioning
confidence: 99%
“…To study the effects of thermal stress on morphogenesis, dissection and direct observation of embryos is critical. Based on our results and comparisons with mammals (Walsh et al., ; Edwards, ; Hutson et al., ), these may be the most thermally sensitive stages of embryonic development for diverse vertebrate species. Within mammals and birds, thermal stress during morphogenesis may cause craniofacial abnormalities, neural tube defects, or mental retardation (Webster & Edwards, ; Shiota, ; Walsh et al., ; Edwards, ; Edwards, Saunders, & Shiota, ).…”
Section: Discussionmentioning
confidence: 99%
“…Supporting their theoretical calculations, Duret et al (2017) show that the calcium response to magnetic field treatment is lost in cells expressing a temperature-insensitive TRPV4-ferritin construct. Similarly, Hutson et al (2017) show that the calcium response to oscillating magnetic field treatment is also lost in cells expressing a temperature-insensitive TRPV1 fused to a ferritin-binding domain. Although this mechanism is plausible, additional magnetomechanical and magnetothermal mechanisms of ion channel activation by iron-loaded ferritin are under consideration (M Barbic, in prep.).…”
Section: Genetically Encoded Particlesmentioning
confidence: 80%
“…Electromagnetic fields can penetrate tissue and in birds and other animals will guide migration, although the precise mechanism is unknown (Freake et al 2006). More recently, it has been shown that electromagnetic fields can be used to regulate the activity of cells in proximity to external metal nanoparticles (Huang et al 2010;Chen et al 2015), or that express genetically encoded intracellular metal nanoparticles (ferritin) (Stanley et al 2015;Wheeler et al 2016;Duret et al 2017;Hutson et al 2017). In both cases, the particles transduce electromagnetic fields that gate ion channels, although the field strength that is required is much larger than that required for magnetic sensing by biologic systems.…”
Section: Electromagnetic Control Of Cell Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…17 However, our results support assumption that increasing the duration of temperature elevation may lower threshold for malformations to 40-41°C 19 as has been recently published for the chick embryo. 74 Other in vitro studies on mammalian skeletal muscle cells have shown that hyperthermia at 41°C for 72 hours inhibited myotube formation. 75…”
Section: Discussionmentioning
confidence: 99%